Exploring the community impact of research-practice partnerships in education - Reardon, R. Martin; Leonard, Jack, 1948- (Current perspectives on school/university/community research., 2017)
This volume explores the impact of research-practice partnerships in education (broadly conceived) on communities in which such partnerships operate. By invitation, some of the partnerships celebrated in this volume are firmly established, while others are more embryonic; some directly engage community members, while others are nurtured in and by supportive communities. Collectively, however, the eleven chapters constitute a range of compelling instances of knowledge utilization (knowledge mobilization), and offer a counter-narrative to the stereotypical divide between researchers and practitioners.Educational researchers and educational practitioners reside in and are both politically supported and socially sustained by their local communities. The nesting of researchers' and practitioners' collaborative decision-making and action in the financial, social, organizational, and political contexts of the community--together with the intended and unintended outcomes of those decisions and actions--speaks to the essence of community impact in the context of this volume.